STRENGTHENING ANTI-CORRUPTION EDUCATION FOR HIGH SCHOOL STUDENTS THROUGH THE INTEGRATION OF INTEGRITY VALUES IN CIVICS EDUCATION - Uma.S (SMART: Journal of Multidisciplinary Educational, 2025)
This study aims to examine how integrity values can be effectively integrated into the Civics Education (PPKn) curriculum to strengthen anti-corruption education among senior high school students in Indonesia. Using a qualitative library research method, this study systematically reviewed and synthesized recent literature, educational policy documents, and national curriculum frameworks published within the last five years. The findings reveal that although integrity values such as honesty, responsibility, and fairness are mentioned in curriculum standards, their actual implementation in teaching practices, assessment tools, and school culture remains fragmented and inconsistent. Teachers often lack specific training in anti-corruption pedagogy, and existing assessments tend to focus on cognitive knowledge rather than ethical reasoning or behavioral outcomes. This study introduces a novel approach by linking curriculum content, teaching strategies, assessments, and institutional support into a cohesive framework for embedding integrity education in PPKn lessons. Unlike previous studies that treat anti-corruption education as a separate module or focus only on elementary levels, this research focuses specifically on the high school context and subject-specific integration. The study concludes that a comprehensive integration strategy—including curriculum revision, teacher capacity building, ethical assessment tools, and supportive school leadership—is essential to transforming integrity values from abstract policy into lived student behavior. The findings offer theoretical and practical contributions that are relevant not only to Indonesia but also to other educational systems seeking to institutionalize anti-corruption education through civic learning.